Dynamic Approach for Diversification Effectiveness Evaluation of Berezovsky Company Town; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Antonova I. S. Irina Sergeevna (2016, 2016)
Title screen